The effect of carbonized rice straw levels on the dawet gel properties - Erni Sofia Murtini (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Merang, part of rice straw, waste generated from rice harvesting process, is abundantly available in Indonesia. Incomplete burning of merang generates carbonized rice straw (CRS). This study is aimed to identify selected minerals (K,Ca, Na and Fe) contents of CRS using AAS, and to evaluate the effect of differentconcentrations (1.5-3%) of CRS addition on the pasting properties of rice:sago mixflour (55:45), and on the black color intensity, texture, and sensory properties of dawet gel. CRS contains potassium (20599.91±776.44 ppm), calcium (307.58±70.71), sodium (30.59±1.03ppm) and iron (1079.98±20.75 ppm). Despite the temperature similarity, pasting properties of mixed flour such as final viscosity and peak time are significantly decreased in response to CRS addition. Increase in CRS concentration results to significant increase of the black color intensity and texture of dawet gel. Sensory evaluation suggests that most of the panelists prefer the color and firmness showed by dawet gel with addition of 2.5% of carbonized rice straw. This result suggests that CRS could be an interesting new food ingredient for increasing black color intensity and texture of food product.